A case of successful cryoballoon ablation of paroxysmal atrial fibrillation originating from a persistent left superior vena cava. Issue 3 (September 2019) - Fujino, Tadashi; Yuzawa, Hitomi; Kinoshita, Toshio; Shinohara, Masaya; Okishige, Kaoru; Ikeda, Takanori
Abstract: We present a paroxysmal atrial ﬁbrillation (AF) patient who had frequent AF events originating from a persistent left superior vena cava (PLSVC) with an unsuccessful catheter ablation using a non-irrigated radiofrequency catheter and was successfully cured by a successful PLSVC isolation using a second-generation cryoballoon catheter (28-mm, second-generation cryoballoon, Arctic Front Advance, Medtronic, Minneapolis, MN, USA). <Learning objective: This is the ﬁrst case report illustrating a successful ablation of a persistent left superior vena cava in a patient with drug-resistant atrial ﬁbrillation (AF) using a second-generation cryoballoon (CB) with a good outcome. By choosing an appropriate position and attaching the CB fixedly, the CB ablation was able to cure the AF smoothly without any complications including left phrenic nerve palsy or left coronary artery stenosis. An intracardiac electrocardiogram and 3-dimensional mapping system could detect conducted ectopic beats initiating AF.>